2007
DOI: 10.1590/s0102-311x2007001000022
|View full text |Cite
|
Sign up to set email alerts
|

O anacronismo dos modelos assistenciais para os idosos na área da saúde: desafios para o setor privado

Abstract: O Brasil envelhece rapidamente. A expectativa média de vida se amplia de tal forma que grande parte da população atual irá alcançar a velhice. Os grandes centros populacionais brasileiros, entretanto, ainda não dispõem de uma infra-estrutura de serviços que dê conta das demandas decorrentes das transformações demográficas vigentes. O propósito deste texto é o de verificar o padrão do acesso e utilização de saúde no grupo etário dos idosos, com particular ênfase no setor privado. Foram utilizadas as informações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
39

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 4 publications
0
20
0
39
Order By: Relevance
“…1,2 The prevalence of chronic diseases increases with age, which reinforces the importance of health prevention interventions targeting healthy habits and better quality of life. 3 According to the National Survey by Household Sampling (PNAD) -IBGE, in 2003, 29.9% of the Brazilian population claimed to be suffering from at least one chronic disease, such as: spinal or back disease, arthritis or rheumatism, cancer, diabetes or hyperglycemia, bronchitis or asthma, hypertension, heart disease, chronic kidney disease, depression, tuberculosis, tendonitis or tenosynovitis, and cirrhosis. 3 Diabetes mellitus (DM), systemic arterial hypertension (SAH), and obesity (OBES) have had a high incidence in the last years.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The prevalence of chronic diseases increases with age, which reinforces the importance of health prevention interventions targeting healthy habits and better quality of life. 3 According to the National Survey by Household Sampling (PNAD) -IBGE, in 2003, 29.9% of the Brazilian population claimed to be suffering from at least one chronic disease, such as: spinal or back disease, arthritis or rheumatism, cancer, diabetes or hyperglycemia, bronchitis or asthma, hypertension, heart disease, chronic kidney disease, depression, tuberculosis, tendonitis or tenosynovitis, and cirrhosis. 3 Diabetes mellitus (DM), systemic arterial hypertension (SAH), and obesity (OBES) have had a high incidence in the last years.…”
Section: Introductionmentioning
confidence: 99%
“…1 Este processo traz como desafio lidar com agravos como doenças crônico-degenerativas e seu enfrentamento requer práticas em saúde que se voltem para a promoção de saúde, prevenção e identificação precoce de fatores de risco conhecidos, conforme indicado pela Política Nacional de Saúde da Pessoa Idosa (PNSPI). 2,3 Mais de um terço das pessoas com idade igual ou superior a 65 anos apresenta uma queda ao ano e em muitos casos esta é recorrente. 4 As quedas podem ser classificadas pela sua frequência, pelas consequências que acarretam, ou de acordo com seu fator de gênese: intrínsecos, extrínsecos e ambientais.…”
Section: Introductionunclassified
“…According to this author, there is a crisis in the current model, adopted in various countries, according to which one has to lose for another to gain. In a recent analysis of the current system all over the world, Porter 11 concluded that the greatest problem is the focus on treating illness to the detriment of prevention, which leads to a win-lose relationship in which someone always has to foot the bill. Porter & Teisberg 21 presented a new Health Care Cycle, in which health precedes care and affi rm that underlying it is the need to measure and minimise the risk of illness, offer comprehensive disease management and make preventative services available to everyone, including the healthy ones.…”
Section: Managing Chronic Illnessmentioning
confidence: 99%